(untitled) (Hekima Review, 1992)
The school of life portrays all things as unendingly passing; life itself and all that it entails is subject to this undying flow of events. Human growth itself is a classic of this procession: from birth humans are, almost contrary to their will, catapulted into the process of growth: physically, mentally, spiritually, in short, nothing is excluded. This course of events is perceived as culminating in death: yet death, regarded as transformatory, is paradoxically a source of new life. Jesus sums it thus; "Unless the grain of wheat falls on the ground and dies..."